2006
DOI: 10.1007/s00467-006-0158-7
|View full text |Cite
|
Sign up to set email alerts
|

First urinary tract infection in neonates, infants and young children: a comparative study

Abstract: In an attempt to evaluate first urinary tract infection (UTI) in neonates and infants, we estimated retrospectively in 296 patients (62 neonates and 234 infants) clinical and laboratory findings, occurrence of vesicoureteral reflux (VUR), urinary tract abnormalities and pyelonephritis. First UTI occurred more often in male than female neonates, whereas male and female infants/young children were affected at an equal rate. The pathogens isolated in urine cultures of neonates and infants did not statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
2
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 40 publications
7
43
2
9
Order By: Relevance
“…The mean age at diagnosis was 16 days, which is consistent with data reported by others [7,16]. In agreement with other studies [10,[16][17][18], UTI was significantly more common in males than in females, particularly in patients with nosocomial UTI. The higher prevalence in males has been explained by the presence of phimosis, increased incidence of nephrourological anomalies, and higher susceptibility to infection [19][20][21].…”
Section: Discussionsupporting
confidence: 93%
“…The mean age at diagnosis was 16 days, which is consistent with data reported by others [7,16]. In agreement with other studies [10,[16][17][18], UTI was significantly more common in males than in females, particularly in patients with nosocomial UTI. The higher prevalence in males has been explained by the presence of phimosis, increased incidence of nephrourological anomalies, and higher susceptibility to infection [19][20][21].…”
Section: Discussionsupporting
confidence: 93%
“…However, an association between urinary tract infection in children with vesicoureteral reflux and renal scarring remains unquestionable (Faust et al, 2009;Jahnukainen et al, 2005;Muinuddin et al, 2008). This was confirmed by recent studies that demonstrated an increase in the risk of renal scarring after acute pyelonephritis in patients with vesicoureteral reflux (Kanellopoulos et al, 2006;Lee et al, 2006;Polito et al, 2006;Oh et al, 2008). Studies by Svensson et al (2005) and Mohanan et al (2008) disclosed that renal scarring was detected less frequently in infants with vesicoureteral reflux and without urinary tract infection than in those with vesicoureteral reflux and urinary tract infection.…”
Section: Reflux Nephropathysupporting
confidence: 54%
“…Kod novorođenčadi se IUT javljaju u 1-2%, a odnos muškog prema ženskom polu u oboljevanju je od 2,8:1 do 5,4:1. Razlog češćeg oboljevanja muške novorođenčadi i dojenčadi treba tražiti u većoj učestalosti kongenitalnih anomalija urotrakta u muške djece [14,15].…”
Section: Diskusijaunclassified